School-Based 4-H Programming Series: Positive Youth Development (PYD) and Social Emotional Learning (SEL)—How They Complement Each Other - Vanessa Spero (EDIS)
Positive Youth Development (PYD) promotes building life skills, leadership, and relationships, and Social Emotional Learning (SEL) promotes knowledge, responsibility, and caring. Just as 4-H uses PYD as a framework, so schools use SEL. A whole program approach with appropriate curriculum provide the skills necessary for youth to succeed. This new 5-page publication of the UF/IFAS 4-H Youth Development Program explores the complementary relationship between PYD and SEL in a school-based program setting. Written by Vanessa Spero-Swingle. https://edis.ifas.ufl.edu/4h404